Benefits And Limitations of Medical Tourism Development In Hong Kong: Local residents' perspective - Siu Ching Kwan; Pimtong Tavitiyaman (ACHSM, 2021)
OBJECTIVES: Promoting medical tourism has been discussed by various stakeholders of its destination. High-quality medical products and services is addressed, especially in the Asia Pacific region. This study aims to (1) explore major criteria to establish medical tourism in Hong Kong from the local residents' perspective and (2) examine the benefits and limitations in developing medical tourism in Hong Kong by the local residents' age groups. DESIGN: Target samples were local residents with different age groups who had experienced receiving medical treatment or service in Hong Kong. The self-administered survey with 38 questions was created to explore the local residents' perceptions on various issues of medical tourism development in Hong Kong. Data was collected in April 2021 with the total response rate of 153 respondents. A descriptive analysis and ANOVA test were applied for objective testing. RESULTS: To answer the objectives, the important criteria for medical tourism development in Hong Kong were physician expertise, infrastructure of hospitals, and healthcare quality. The least important criteria were the political and economic condition of that destination and language. The ANOVA results have shown significant differences on the benefits and limitations of developing medical tourism by age groups of local residents. Younger respondents perceived a benefit of medical tourism, rather than elderly respondents in terms of gaining more medical experience. Elderly respondents perceived the limitations of medical tourism development compared to younger respondents in the areas with lacking private sector interest and high cost. CONCLUSION: There are numerous factors for consideration on establishing medical tourism destination in Hong Kong. Local residents perceive an opportunity for Hong Kong as a medical tourism destination. Although some limitations should be closely monitored, local residents would be confident with medical tourism development. (*The paper was presented at The Hong Kong Polytechnic University's College of Professional and Continuing Education (CPCE) Conference "Post-pandemic health and long-term care: A new paradigm". September 2021)